Involvement of Urease-Producing Bacteria on Genital Skin in Community-Dwelling Women with Incontinence-Associated Dermatitis: A Cross-Sectional Study - Kohta M; Sugama J (Journal of Multidisciplinary Healthcare)
Masushi Kohta, Junko Sugama Research Center for Implementation Nursing Science Initiative, Fujita Health University, Toyoake, Aichi, JapanCorrespondence: Junko Sugama, Research Center for Implementation Nursing Science Initiative, Fujita Health University, 1-98 Dengakugakubo, Kutsukake-cho, Toyoake, Aichi, 470-1192, Japan, Tel +81 562 93 2504, Fax +81 562 93 4593, Email junko.sugama@fujita-hu.ac.jpPurpose: Elevated skin pH facilitates the number of pathogenic bacteria increase, leading to the skin barrier dysfunction. This phenomenon is typically observed in individuals with Incontinence-associated dermatitis (IAD), which imposes a substantial physical and psychological burden on the afflicted individuals. We evaluated the association between the development of IAD in community-dwelling women with urinary incontinence and cutaneous urease-producing bacteria, as these bacteria may be involved in elevating skin pH by chemical reaction with urea in urine.Patients and Methods: This was a cross-sectional study of 114 community-dwelling women with urinary incontinence who had registered for a survey campaign of a company. Swabs collected from genital skin were cultured in urea agar medium. The presence of urease-producing bacteria was determined by visually observing the change in the color of the culture medium caused by alkalization. The medium pH and total bacteria count were measured. Bacterial species were isolated and identified using a selective agar medium and simple identification kits. The participants were asked the presence of IAD by a self-administered questionnaire, and outcomes were compared between the IAD and no-IAD groups. This study followed the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) guideline.Results: IAD was present in 31.6% (36/114) of participants. The detection rate of urease-producing bacteria and the medium pH was significantly higher in the IAD group than in the no-IAD group; however, the total number of bacteria was not significantly different. There were no significant between-group differences regarding the bacterial species identified.Conclusion: The presence of urease-producing bacteria was associated with the development of IAD in community-dwelling women with urinary incontinence. Alkalization of the genital skin surface because of the contact between urine and urease-producing bacteria may compromise skin homeostasis. The bacterial species specifically involved in the development of IAD could not be determined.Keywords: microorganism, perineal, pH, skin care, women’s health